Herbicides selectivity in pre-budded seedlings of sugarcane - Dias, José Luiz Carvalho De Souza (2017)
ABSTRACT: Herbicides are expected to show selectivity towards cultivated plants, i.e., they ought to control weeds without jeopardizing the development and productivity of crops. The objective of this project was to evaluate the selectivity of herbicides applied in pre-planting of three sugar cane cultivars which were planted according to the system of pre-budded seedlings (PBS) under climatic natural conditions, between September and November of 2013. The experiment was set according to a completely random design with four replications. The treatments were distributed according to a factorial scheme of 3 × 8, in which factor A was the cultivar (CTC14, CTC7, and RB966928), and factor B was the herbicide (in g.ha-1): S-metolachlor (2,640), clomazone (1,000), sulfentrazone (800), diclosulam (200), metribuzin (1,920), diuron + hexazione (1,170 + 330), S-metolachlor + sulfentrazone (2,640 + 800), and a no treatment. The visual symptoms of intoxication were evaluated 14, 28, 35, 42, 49, 56, and 63 days after application (DAA), the height and number of tillers 14, 35, 49, 56, and 63 DAA, the dry weight of shoot (DWS), and the dry weight of root (DWR) 63 DAA. Under the conditions of the experiment, the herbicides S-metolachlor, clomazone, metribuzin, diuron + hexazinone, and S-metolachlor + sulfentrazone were selective towards the presprouted sugar-cane plantlets. Diclosulam was the less selective herbicide, followed by sulfentrazone. Cultivar CTC14 was visually the less tolerant to the herbicides diclosulam and sulfentrazone.